Source-sink relationship of soybean accessed by increasing in solar radiation through the plant canopy - Fioreze S.L. (2022)
© This is an open access article under the CC BY license Creative CommonsThe photosynthetic metabolism is a key point to improve soybean yield. In this work, we demonstrated that radiation use by soybean plants can be improved, aiming to improve the grain yield in the lower canopy. The objective of this study was to observe whether the increase in solar radiation input in the canopy of soybean plants improves their yield performance. Three experiments were carried out during the 2017/2018 season. For each experiment, treatments consisted in the opening of one or two side rows of cultivation at the R2 and R5 stage of soybean plants (NA5909RR) until maturity, plus a control. Increase on solar radiation provided by the oppening of rows enhanced the yield potential in the nodes of the lower canopy, mainly when two rows were opened. The main benefits of increasing the radiation available throughout the canopy of soybean plants are observed in the number of pods and thousand-grain weight, demonstrating the importance of increasing the availability of assimilates in lower leaves. Interestingly, the benefits of the increase in solar interceptation were observed regardless of the yield potential of the area, which varied between 4.9 and 6.7 ton ha-1.